Paciente de sexo masculino de 50 años de edad con diabetes mellitus tipo ii - Villaprado Vera, Janeth Mercedes (2020)
Diabetes mellitus is a multifactorial disease is a disease highly associated with loading genetics and environmental factors, most of the food we eat is converted to glucose and it is used by the body to generate energy, the pancreas is the main organ that is in charge of the production of insulin, this is a hormona that transports the glucose towards the interior of the cell of our body; Diabetes has serious consequences when not treated in time, increasing the risk of vascular diseases, amputation of the lower extremities, blindness, damage to the kidneys; The present case study is about a woman recently diagnosed with Diabetes mellitus type II, the patient reports that she takes her medication exactly as the doctor indicated, but does not carry out healthy eating habits that help her control, such as diet and physical activity; the nutritional evaluation indicated a BMI of 26.7kg / m2 overweight with increased cardiovascular risk; Her biochemical examinations reflected hyperglycemia, hypercholesterolemia, and hypertriglyceridemia, which is related to the poor lifestyles presented by the patient. An individualized diet plan is provided according to the energy requirement, disease and socioeconomic level of the patient, in order to normalize their glucose levels, the type of diet that will be prescribed will be a diabetic diet divided into 5 meal times, This diet has a characteristic, hypo fat, normoglucid, high in soluble fiber which improves the nutritional state of the patient.